The Effect of Cognitive Ability in Problem-Based Learning on Science Literacy Ability of Grade 4 Elementary School Students - Astri Widyasari; Hermanto Hermanto (STAI Hubbulwathan Duri, 2023)
This research are motivated by the low cognitive ability of learners and followed by low levels of science literacy of science participants. The study's goal was to find out if there was a direct influence on students' cognitive and science literacy abilities. The method in this study is in the form of a test method with an ex-post-facto research design. This research has been done at Sumberagung State Elementary School Yogyakarta with 4th grade A research subjects totaling 32 students. A simple regression technique functioned to analyze the data inferentially. Through a simple regression test, the results of F count = 10,585 and p-value = 0.003 0.05 or H0 are rejected. Thus regression Y over X is a significant cognitive ability to affect a student's science literacy. The coefficient of determination obtained the value R Square = 0.274, which means that students' cognitive ability can influence 27.4% variation in the variable science literacy ability. At the same time, 72.6% of science literacy ability was affected by other variables that were not studied. Other factors can affect the science literacy ability of learners. The researcher hopes that further research can improve this research.